Chronic pancreatitis with pseudocysts? Chronische Pankreatitis mit Pseudozysten? - Veits, L.; Vieth, M.; Agaimy, Abbas (Pathologe, 2013)
The gross examination of cystic changes in chronic pancreatitis can cause diagnostic problems particularly in the absence of grossly detectable tumor tissue. Besides the more frequently encountered pancreatitis-associated pseudocysts, pancreatic cysts should always raise attention to the differential diagnosis of a true neoplastic process. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Chronic pancreatitis; Intraductal neoplasia; Intraductal papillary mucinous neoplasm; Pancreatic intraepithelial neoplasia; Pseudocysts